2020
DOI: 10.3390/en13071576
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Production from Amino Acid Wastes by the Oleaginous Yeast Rhodosporidium toruloides

Abstract: Microbial lipids have been considered as promising resources for the production of renewable biofuels and oleochemicals. Various feedstocks, including sugars, crude glycerol, and volatile fatty acids, have been used as substrates for microbial lipid production, yet amino acid (AA) wastes remain to be evaluated. Here, we describe the potential to use AA wastes for lipid production with a two-stage culture mode by an oleaginous yeast strain Rhodosporidium toruloides CGMCC 2.1389. Each of the 20 proteinogenic AAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…Among others, the oleaginous yeasts are considered as potential lipid producers due to their higher growth rate, adaptation to diverse substrates, and higher lipid production yields. Until now, various organic substrates including waste cooking oils [ 8 ], different biomass derived sugars [ 9 ], amino acid-rich wastes [ 10 ], and industrially produced organic wastes [ 11 ], have been utilized for microbial lipid production. However, the high production cost of microbial lipid technology prevent its broader commercialization [ 12 ], where the fermentation processes and substrate costs are significant to lipid production [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among others, the oleaginous yeasts are considered as potential lipid producers due to their higher growth rate, adaptation to diverse substrates, and higher lipid production yields. Until now, various organic substrates including waste cooking oils [ 8 ], different biomass derived sugars [ 9 ], amino acid-rich wastes [ 10 ], and industrially produced organic wastes [ 11 ], have been utilized for microbial lipid production. However, the high production cost of microbial lipid technology prevent its broader commercialization [ 12 ], where the fermentation processes and substrate costs are significant to lipid production [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…1). We previously demonstrated successful lipid production with AA blends matching a similar AA compositional profile to sheep viscera AA (SVAA), 35 fish muscle AA (FMAA), 36 or meat industry by-product AA (MIAA), 37 as carbon substrates; 23,24 however, it was found that AA in high concentrations had adverse effects on cell viability and lipid production, which might have been due to the high osmotic stress, high intracellular AA level, 42 accumulation of ammonia or inhibitory metabolic intermediates, 43,44 or the very low C/N ratio of the media, as the C/N ratio of about 100 was found to be favorable for lipid production. 21,22 To improve the C/N ratio of the media and subsequently encourage microbial lipid production on AA, 20 g L -1 glycerol was supplied to the media containing the designated AA blends with similar AA compositions to SVAA, FMAA, and MIAA, respectively (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Glycerol addition improved the lipid production and maintained relatively high cell mass compared with our previous results using FMAA blends for lipid production. 23,24 The highest AA consumption of 37.1 g L -1 (61.5%) was observed using MIAA with 8.8 g L -1 (44.2%) glycerol consumption. The C/N ratio of 5.2 was relatively high compared with other AA blends but the low lipid yield of 6.9 g 100 g -1 might have been due to the high substrate concentration in the media (Table 2, entry 3).…”
Section: Y S G Ln a S N A La T H R G Ly V A L S E R P R O Il E L E U M E T H Is P H E G Lumentioning
confidence: 97%
See 1 more Smart Citation
“… 2010 ; Li et al . 2020 ). To accumulate high amounts of lipids, oleaginous yeasts are usually cultivated under nitrogen-limited conditions (Evans and Ratledge 1984 ).…”
Section: Introductionmentioning
confidence: 99%